Causality Analysis of Interest Rates, Inflation, Economic Growth and Household Consumption in Indonesia from 1992 to 2022 - Mahdi, Aagym Fauzan; Samsudin, Muhammad Afdal (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2024)
The aim of this research is to determine the influence of inflation, interest rates and economic growthon household consumption in Indonesia from 1992 to 2022. The research method used in this researchis the Vector Autoregressive (VAR) analysis method. The results of this research partially show thevariables of inflation, interest rates, economic growth. there is a complex causal relationship betweenthe economic variables analyzed. Monetary policy that increases interest rates can help reduceinflation and encourage stable economic growth. High inflation can cause Bank Indonesia to raiseinterest rates and encourage household consumption. Strong economic growth can increasehousehold income and encourage consumption. Increased household consumption can increasedemand for goods and services, which in turn can encourage inflation.